The Dynamics of Welfare Participation among Women Who Experienced Teenage Motherhood in Australia - Vu, Ha; Kalb, Guyonne; Jeon, Sung Hee; Vu, H (My University, 2011)
We examine whether the factors that determine the welfare participation of women who experienced teenage motherhood differ from those determining the welfare participation of women whose first birth was at an older age. Using a dynamic random effects probit model, we find evidence of state dependence in welfare participation for all mothers, but it is relatively stronger for women who experienced teenage childbearing. In addition, counterfactual decomposition shows that, conditional on welfare receipt, differences in the characteristics of the two groups of mothers explain a larger proportion of the differences in their welfare dependency relative to differences in their behaviour.
Economic Record
Keywords: Benefits and Payments; Families -- Mothers; Families and relationships; Families; Benefits and Payments; Mothers; Families and relationships